Edukasi Isi Piringku Sebagai Pemenuhan Gizi Seimbang di Masyarakat Nelayan Kota Tegal - Oktariani Pramiastuti; Ratna Widhiastuti; Anggit Pratiwi; Eni Purwiastuti; Grace Monica; Aurelia Neysa Putri Nirwana; Radinka calista Anggita; Siti Rachmalia; Yudistira Rifki Ramdhani (JABI: Jurnal Abdimas Bhakti Indonesia, 2026)
Public health status can be assessed through various factors, including life expectancy, mortality rates, morbidity rates, and nutritional status. One way to improve health status is by enhancing the community's nutritional status. The "Isi Piringku" concept, emphasizing balanced nutrition, needs to be introduced and integrated into daily life. In a single meal portion, half the plate should consist of vegetables and fruits, while the other half contains protein sources (both plant- and animal-based) in proportions exceeding that of carbohydrates. Mothers often provide meals that are insufficient in quantity and lack variety, causing family members to become bored and refuse to eat. This community service activity aims to increase the knowledge and understanding of PKK members regarding the fulfillment of balanced nutrition through the "Isi Piringku" concept using local food sources. The implementation method involved planning, preparation, and execution stages carried out participatively with the local sub-district government and the community. The "Isi Piringku" education aims to improve public understanding of balanced nutritional portions (half the plate for vegetables and fruits; the other half for carbohydrates and side dishes) to prevent disease, address nutritional issues (such as stunting), and encourage a healthy lifestyle. Evaluation results indicate an increase in mothers' knowledge following the intervention, reflecting positive behavioral changes regarding the fulfillment of balanced nutrition through the local food-based "Isi Piringku" approach. It can be concluded that "Isi Piringku" education influences the knowledge and understanding of PKK members regarding the selection of balanced-nutrition menus and family meal provision. Following this education, PKK members and parents are expected to implement feeding practices that meet nutritional needs in accordance with the "Isi Piringku" food presentation concept.